Inter-tester reliability assessment of the volumetric measurement of the hand in subjects without any changes in their upper extremities - Ribeiro, Renata Cristina Boffi; Lima, Simone Maria Puresa Fonseca; Carreira, Ana Cláudia Gomes; Masiero, Danilo; Chamlian, Therezinha Rosane (Acta Fisiátrica, 2010)
The purposes of the present study were to evaluate the inter-testerreliability of the volumeter and to determine the normative index in adults of both genders and without any changes in their upper limbs. The sample was composed of one hundred individuals (200 hands), 50 women and 50 men, with ages between 21 and 50, and with uncompromised upper limbs. The volume of each subject’s hand was randomly measured through the volumetric method and the instrument used to evaluate them was a volumeter. This method was applied by 2 examiners and each patient was evaluated twice. Comparing the hands, gender, and examiners, we can observe that the mean of the right hands was always greater than that of the left hands, the mean volume of men’s hands was always greater than the women’s, and the mean of the second examiner was always greaterthan the first. From this analysis, considering values obtained with both examiners, we can notice that the final average was significant (p<0.001) to the difference between the right and the left hand in the general population, for women and for men. We can conclude that the results statistically significant to the final averages of volumetry were: for women, right hand with 402.40ml and left with 397.15ml; for men, right hand with 516.10ml and left with 505.30ml, and, in the general population, right hand with 459.25ml and left hand with 451.23ml. We can also conclude that the results are cohesive and reliable.